Manajemen Strategi Pada Lembaga Kursus Dan Pelatihan (LKP) Dessy Kecamatan Bergas - Rina Purwanti; Purwosiwi Pandansari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This research is a type of qualitative descriptive research, because in this research it will describe the condition of the object and the researcher plays the role of being the key instrument that will process the data. This research was carried out naturally, this research chose to focus on the conditions existing at the Dessy Course and Training Institute (LKP), Bergas District. The data collection technique in this research uses 3 data collection techniques, namely semi-structured interviews, documentation and triagulation. The data sources in this research are subject sources who have the information needed to support this research, namely managers, teachers, employees, members and alumni of LKP Dessy. LKP is a form of non-formal education unit organized for people who need knowledge, skills, life skills and attitudes to develop themselves, develop their profession, work, do independent business and/or continue their education to a higher level. In carrying out the LKP, good management is also required, namely in the selection of management strategies by the management. Strategic management is a series of managerial decisions and actions that determine company performance in the long term. Strategic management includes long-term planning, strategy implementation, evaluation and control. This research aims to qualitatively describe strategic management at LKP Dessy, Bergas District. The results of the analysis show that strategic management at LKP Dessy can be described using one of the stages in company development, namely strategic management whose components include environmental observation, strategy formulation by determining the LKP program plan, LKP program planning, strategy implementation, evaluation and control.